2012
DOI: 10.1097/mpg.0b013e318248e7be
|View full text |Cite
|
Sign up to set email alerts
|

Protective Antibody Responses to Influenza A/H1N1/09 Vaccination in Children With Celiac Disease

Abstract: Patients with celiac disease have an increased risk for severe influenza infection and they show less of a response to certain vaccine types. During the influenza A/H1N1/09 pandemic, we prospectively investigated pandemic vaccine responses in 14 pediatric patients with celiac disease and age-/sex-matched controls. All of the children with celiac disease reached protective antibody titers (≥40) and showed a geometric mean titer comparable with the control group (530 vs 573).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Studies in patients with type 1 diabetes, celiac disease, and IBD showed that individuals with these IMDs who are not treated with immunosuppressive agents generally have comparable serologic responses to vaccination as healthy individuals. 17-20 As several DMARDs and biologic agents interfere with the immune response to vaccines (Figure 1, Figure 2, Table 2, and Table 3), it is imperative to assess the patient’s immunization history at diagnosis and administer age- and disease-appropriate vaccines according to local guidelines prior to treatment initiation to optimize efficacy. Concerns regarding the risk of disease exacerbation are unfounded as studies have shown that immunization did not generally cause clinically significant worsening of underlying IMDs (Tables 2 and 3).…”
Section: Evidence Summarymentioning
confidence: 99%
“…Studies in patients with type 1 diabetes, celiac disease, and IBD showed that individuals with these IMDs who are not treated with immunosuppressive agents generally have comparable serologic responses to vaccination as healthy individuals. 17-20 As several DMARDs and biologic agents interfere with the immune response to vaccines (Figure 1, Figure 2, Table 2, and Table 3), it is imperative to assess the patient’s immunization history at diagnosis and administer age- and disease-appropriate vaccines according to local guidelines prior to treatment initiation to optimize efficacy. Concerns regarding the risk of disease exacerbation are unfounded as studies have shown that immunization did not generally cause clinically significant worsening of underlying IMDs (Tables 2 and 3).…”
Section: Evidence Summarymentioning
confidence: 99%
“…A prospective study on vaccination against influenza A/H1N1/09 among children with CD ( n = 14) and age-matched healthy controls ( n = 14) showed that CD patients achieved protective antibody titers comparable to the control group [ 52 ].…”
Section: Vaccination Immunogenicitymentioning
confidence: 99%
“…In addition, children with CD have a higher risk of influenza infection and secondary hospital admission[21]. The increased infection risk in CD patients is probably due to several factors.…”
Section: Celiac Disease and The Risk Of Infectionsmentioning
confidence: 99%
“…The lack of response among CD subjects to HBV vaccination is important for public health policies because these non-responders may be a reservoir for HBV[43]. The published studies on the association between CD and HBV vaccination in children are presented in Table 1[11-21,24]. In the earliest report, involving 26 celiac patients aged 9.2 ± 4.6 years and 18 age-matched controls, receiving the full complement of childhood vaccination (HBV, tetanus, rubella, Haemophilus influenzae type b), Park et al[11] showed that a significantly greater percentage of children with CD did not respond to HBV vaccination in comparison with controls (53.9% vs 11.1%, P < 0.05).…”
Section: Responses To Vaccinations In Children With Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation